Pattern of Electromyographic Activity in Mastication Muscles of Adolescents with Temporomandibular Disorder - Lauriti, Leandro (The Society of Physical Therapy Science, 2013)
[Purpose] The aim of the present study was to assess the behavior of the mean and median frequencies of the electromyography signal of the mastication muscles of adolescents with different degrees of TMD severity. [Subjects] Forty-two adolescents aged 14 to 18 years. [Methods] The adolescents were classified according to severity using the Helkimo Index. The control group consisted of 14 subjects with no signs or symptoms of TMD. Three readings were taken in during maximum intercuspation and mandibular rest, with each reading lasting 10 seconds. [Results] Significant differences (p=0.0001) were found in the mean frequency (Hz) between the control group (CG), mild TMD group (MG) and moderate/severe TMD group (MSG), especially during mandibular rest, for all muscles evaluated: right temporal: CG (137.5), MG (194.2), MSG (291.7); left temporal: CG (106.9), MG (200.6), MSG (294.2); right masseter: CG (155.7), MG (242.8), MSG (278.3); left masseter: CG (125.0), MG (214.6), MSG (316.7). Greater differences among groups were found under the condition of mandibular rest. Conclusions: Adolescents with TMD especially those with more severe symptoms exhibit hyperactivity of the mastication muscles.